Proteomic Investigations of Complex I Composition: How to Define a Subunit? - Meyer, Etienne H. (Frontiers in Plant Science, 2012)
Complex I is present in almost all aerobic species. Being the largest complex of the respiratory chain, it has a central role in energizing biological membranes and is essential for many organisms. Bacterial complex I is composed of 14 subunits that are sufficient to achieve the respiratory functions. Eukaryotic enzymes contain orthologs of the 14 bacterial subunits and around 30 additional subunits. This complexity suggests either that complex I requires more stabilizing subunits in mitochondria or that it fulfills additional functions. In many organisms recent work on complex I concentrated on the determination of its exact composition. This review summarizes the work done to elucidate complex I composition in the model plant Arabidopsis and proposes a model for the organization of its 44 confirmed subunits. The comparison of the different studies investigating the composition of complex I across species identifies sample preparation for the proteomic analysis as critical to differentiate between true subunits, assembly factors or proteins associated with complex I. Coupling comparative proteomics with biochemical or genetic studies is thus required to define a subunit and its function within the complex.